Identifying Strategic Issues for Lecturer Development at the Raden Mas Said State Islamic University Surakarta, Indonesia - Sukamti, Wahyu (CV. Jendela Edukasi Indonesia, 2025)
Improving the quality of lecturers has a strategic role in improving the quality of tertiary institutions. One of the efforts to improve the quality of lecturers is by formulating a lecturer development strategy in improving the quality of the tri dharma of higher education. This study aims to analyze lecturer development strategies in improving the quality of the tri dharma of higher education. The approach used is qualitative with a descriptive analysis method with the object of research being one of the PTKIN in Central Java, namely Raden Mas Said State Islamic University Surakarta. The techniques applied in collecting this data are interviews, observation, and documentation. The results of this study indicate that using the SWOT analysis, a lecturer development strategy can be formulated, namely, (1) The lecturer development program is following science and technology and the vision, mission, and objectives of Raden Mas Said State Islamic University, (2) Integration-based learning, (3) Providing funding for research projects or initiatives with an interdisciplinary approach, holding internship-like programs. (4) Research and publication assistance, (5) Provision of scientific-based community service, and (6) Acceleration of doctoral programs and acceleration of professors.